Mapping the Peak Ground Acceleration Value and Seismic Intensity in Pesisir South District Area using The Empirical Formulation of SI and Midorikawa - Fauzi, Muhammad Aulia; Syafriani, Syafriani (Department of Physics, Universitas Negeri Padang, 2024)
The South Pesisir is an area that is prone to earthquakes, because it is in a zone that is traversed by the Sumatran fault, subduction zone and Mentawai fault. The 3 earthquake zones are areas that have an active level of seismicity from which the maximum ground acceleration value and earthquake intensity can be calculated. This research aims to determine and map the peak ground acceleration and seismic intensity values ​​to support development planning and spatial planning in the South Pesisir District area.This type of research is descriptive research, namely by collecting earthquake catalog data sourced from the USGS (United States Geological Survey) in the period 1973-2023 with coordinates -2.35°S – -1.04°N and 99.32°E – 101.27°E . The magnitude used is M ≥ 5 SR and a maximum depth of 300 Km. The method used in processing the peak ground acceleration data is the empirical formulation of Si and Midorikawa attenuation, then the peak ground acceleration and seismic intensity data output is displayed with ArcGis 10.8 software.The results obtained from calculating the higgest peak ground acceleration were in Lengayang District, Air Pura District, Pancung Soal District, and Basa IV Balai Tapan District with a value of 225.53 – 526.57 gal, while the lowest ground acceleration value was in Koto XI Tarusan District , Bayang District, North Bayang District, and Silaut District with a value of 16.15 – 27.91 gal. Meanwhile, the highest seismic intensity is in Lengayang District VIII MMI and the smallest seismic intensity is in Bayang District, North Bayang District, and Silaut District, namely IV MMI.